A Clinical Study of Labour and Outcome in Hundred Cases of Primigravida in Dhaka Medical College and Hospital - Fatema, Kaniz; Ghani, Tabassum; Paul, Subinoy Krishna; Noorjahan, -; Begum, Afrina; Hussain, Taufiqua (Journal of Dhaka Medical College, 2018)
Introduction: Primigravida is one, who is pregnant for the first time. A successful well managed vaginal delivery first time around usually leads to subsequent deliveries being relatively uneventful. Conversely, a poorly managed first labour can add to subsequent obstetric problems. Therefore, utmost care and expertise is a predominant factor for a successful delivery. Aims and objectives: Objectives of this study is to enhance the rate of safer delivery for primigravida through monitoring progress of labour, mode of delivery and fetomaternal outcome. Methodology: This prospective study was carried out at labour ward in the Department of obstetrics and Gynaecology of Dhaka Medical College & Hospital from January, 2007 to June 2007. Hundred cases of primigravida were selected for this study. Data had been collected through questionnaires. Results : Largest number of patients (50%) had age group 20-24 years and likely to have normal vaginal delivery. Sixty percent patients had regular antenatal check up. Risk factors like PIH, Breech presentation, Face presentation, Rh negative, Jaundice and Pyrexia were found in 23% cases.About 96% fetuses presented by vertex, among them 52% had non engaged head. Sixty patients came with cervix at or less 3 cm dilated and 40 patients were at cervical dilatation 4 cm or more. Progress of labour was monitored by modified WHO partograph. Sixty two percent patient delivered vaginally, among them 3% patients need instrumental delivery. Thirty eight patients pregnancy were terminated by caesarean section. Ninety nine percent babies were live birth and 1% was still birth. Conclusion :Safest age group for delivery of primigravida in this study between 20-24 years. So, women should be encouraged to have their 1st child at this age. People should be made aware of the benefits of proper antenatal check up and choosing safest place for delivery. J Dhaka Medical College, Vol. 27, No.1, April, 2018, Page 9-13